Heteroatom-modulated switching of photocatalytic hydrogen and oxygen evolution preferences of anatase TiO 2 microspheres - Liu, G.; Pan, Jian; Yin, L.; Irvine, J.; Li, F.; Tan, J.; Wormald, P.; Cheng, H. (2012)
Understanding and manipulating the two half-reactions of photoinduced electron reduction and hole oxidation are key to designing and constructing efficient photocatalysts. Here, how the spatial distribution of the heteroatom modulates photocatalytic reduction (hydrogen evolution) and oxidation (oxygen evolution) reaction preferences is investigated by moving boron from the core to the shell of an anatase TiO 2 microsphere along [001] via thermal diffusion control. The preference towards photocatalytic hydrogen and oxygen producing reactions from splitting water can be switched by creating a shell with an interstitial B s+ (s = 3) gradient in the TiO;bsubesub microsphere. This switching stems from the downward shift of electronic band edges of the shell by a band bending effect that originates from the extra electrons coming from the interstitial B;bsupumlesup. These results create new opportunities for designing and constructing efficient photocatalysts by spatial heteroatom engineering. By moving heteroatom boron from the core to the shell of an anatase TiO;bsubesub microsphere via thermal diffusion control, the photocatalysis reaction preferences towards hydrogen and oxygen evolution from water splitting can be sensitively switched. © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.